Metrics and outcomes of conservation education: a quarter century of lessons learned. Issue 2 (1st February 2019) - Thomas, Rebecca E. W.; Teel, Tara; Bruyere, Brett; Laurence, Samantha
Abstract: We conducted a systematic literature review to analyze evaluations of conservation education programs on a global scale in order to better understand (1) temporal and spatial trends in conservation education program evaluations over the last 25 years, (2) patterns in the types of conservation-related issues addressed through these programs, (3) metrics that indicate effectiveness of conservation education programs, and (4) methods and timeframes used to draw conclusions about program outcomes. Findings indicated that there is a need to better connect the types of issues addressed through conservation education programs with metrics that would indicate success in addressing these issues and the actual outcomes measured and reported. As well, there is an opportunity to employ a variety of metrics and methods for evaluating program outcomes, particularly in developing countries, by focusing on cognitive and behavioral components as well as social and ecological ones. Finally, shifting to a more comprehensive strategy for evaluating multiple outcomes in different cultural contexts would provide opportunities for utilizing mixed methods and qualitative approaches in partnership with community stakeholders.